Philip L. Raikes, Livestock Development and Policy in East Africa. Centre for Development Research Publication 6. Uppsala: Scandinavian Institute of African Studies, 1981, 250 s., 40,00 skr. - Dolberg, Frands (Politica, 1982)
-